DYNAMIC GEOTHERMAL EFFECTS AND LOCAL SEISMICITY OF THE TRANSCARPATHIAN REGION - Kravets, S.; Malytskyy, D.; Astashkina, O.; Makhnitskyy, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aim is to obtain quantitative estimates of abnormal variations upon the influence of temperature field tasting and relaxation dynamic effects of seismic origin and their relationship. Regime monitoring of rocks temperature in seismically active areas was performed. Data analysis in the presence of hydrothermal inflows in the region complexed by earthquakes preparations should occur quickly (by hours, weeks to months). These short-term changes in temperature and thermal waters were observed during several strong earthquakes. A number of factors involved in the processes of redistribution of temperature fields in the surrounding rock stations of Carpathian seismic network were investigated. The relationship factors were important to establish and to offset the impact of temperature on geophysical surveys. We produced the desired method of measuring the geothermal gradient in the territory of the Base. To make accurate meteorological observations and temperature regime we applied multi-channel stande-alone digital thermograph that provides relative accuracy of temperature measurement order of 0.01°C. The analysis of long-term observations for geothermal environment in the well at the station of Carpathian Network (CSG Coast) were established. We studied the impact of inflow (source of seismic waves) for modification of the abnormal thermal field in time. The results of the anomalous behavior of the temperature field caused by the transfer of thermal waters inflowes and the mechanical processes and changes in reservoir pressure in the earthquakes area of Vranch zone indicates that there may be a relatively of short-term and substantial amount of thermal field of rocks change. They were caused by redistribution of heat with movement along the channals sources of groundwater during strengthening of tectonic activity.